VARIATION OF GEOCHEMICAL SIGNALS IN CORAL SKELETONS: ENVIRONMENTAL CHANGES OR BIOLOGICAL PROCESSES? - Watanabe Ts.; Reynaud S.; Cuif J.P.; Dauphin Ya. (My University, 2006)
Corals are widely distributed throughout a long stretch of geological time and can provide high-resolution histories of climatic variabilities in the tropics, which play a key role in understanding the Earth's climate system. Geochemical approaches to corals have been widely used for reconstructing palaeoclimates because the geochemistry of the skeleton is believed to vary as a function of several environmental conditions. However, large variations that cannot be ascribed to a single environmental factor have been observed among and/or within calibrations of coral-based proxies. Two main unsolved factors could lead to these large discrepancies: unexpected environmental changes in reefs and unknown biological processes occurring at coral biomineralization sites. In this review, we show the recent progress in dealing with this question by application of coral culture technique and micro analytical methods to skeletal geochemistry in corals and discuss on how the degree of geochemical variation could be affected by environmental changes and how by biological processes during the skeleton's calcification. The next challenge will be to perform high-resolution analysis on cultured corals growing under controlled and/or constant environmental conditions. Such efforts hold the promise of yielding important new insights into the various biomineralization processes that may affect the chemical and isotopic composition of the skeletons, with the goal of understanding how environmental changes express themselves in geochemical variability.
Keywords: BIOMINERALIZATION; CORALS; CULTURE TECHNIQUE; OXYGEN ISOTOPES; PALEOCLIMATES; TRACE ELEMENTS